Utopia in Dystopia: Presentation of the Landscape in Cormac McCarthy’s The Road - Sharma, Prakash (Bon Voyage, 2024)
This paper explores the presentation of the utopian landscape in a dystopian world to impart the message of optimism in Cormac McCarthy’s novel The Road employing the theoretical ideas of ecocriticism focusing on the environmental apocalypse trend. The text as post-apocalyptic fiction presents the earth near destruction in relation to humans, animals and plants world after a frightening apocalypse.  The two unnamed characters journey through the desolate landscape in search of safety. The landscape is full of silence and lifelessness, frightening and unfriendly for survival that tells a terrifying tale indeed. At the same time, the landscape is presented as a major component of the theme. More than that landscape itself is a text that needs interpretation as it has multiple possibilities. The world of the novel is dominated by a dystopian landscape. However, within that deadly world, the world of dream and memory is full of utopian landscape. This contrastive presentation seems purposeful. It is to keep the strand of hope and aware readers about the negative consequences, which the anthropocentric invasion to the natural system invites. Following qualitative research design, this paper uses textual analysis method to interpret the text with the critical ideas of Lawrence Buell related to the environmental apocalypse trend.